A new coalition formation based on reservation prices and locations of buyers - Narabin, Santit; Boonjing, Veera; Boongasame, Laor (My University, 2013)
This paper defines a coalition as a cluster of buyers in dimensional space of reservation price and location. It defines a new buyer utility accounting for discount and traveling costs. A new coalition with nonnegative utility is proposed to maximize a number of successful buyers. This nonnegative utility coalition also assures that a winner does not have to pay more to subsidize others. Simulation results confirm that performance of the new scheme is significantly better than of a random one and is as good as a reservation price based coalition. © 2013 S. Narabin et al.
Keywords: Buyer coalition; Coalition formation; Electronic commerce; Group-Buying; Groupbuymultiple